GAMBARAN PERILAKU MASYARAKAT TERHADAP PENCEGAHAN DEMAM BERDARAH DENGUE (DBD) - Ulfa, Ruvida; Arneliwati, Arneliwati; Erwin, Erwin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
The dengue (DBD) is one of the disease which caused by the dengue virus infection that is transmitted from Aedes Aegypti mosquitoâs where is very dangerous disease that can cause the death. The highest insiden in Pekanbaru is on Kecamatan Bukit Raya with 91 patients, especially in Kelurahan Air Dingin which is 27 patients on 2017. This research aimed to know how the behavior action which is from knowledge, attitude (action), and what are the people do to prevent dengue (DBD). This research used descriptive method with cross sectional approach. This research used 100 samples with using Non probability Sampling Method. The all ellection of a sample using purposive sampling. Where is chosing from endemic area with the cases of DBD consist 3 RW on the Kelurahan Air Dingin. The measuring technique is using questionnaire which is has been doing the validity and realibity test. The data analysis which using in this research consist of univariat analysis. The result of this research showed that 54 respondents (54%) have a good knowledge, most of them have a negative action (attitude) 51 respondents (51%), and a lot of people have a negative response to prevention the dengue (DBD) about 55 respondents (55%). The researcher give a suggestion to the people that they must increase the knowledge so they can do the better action in prevention the dengue (DBD).Keywords : Behavior, DBD, Prevention the dengue (DBD)